Determination of Heavy Metals in Tilapia (Oreochromis Niloticus) and Water Samples from Lake Hayq, South Wollo, Ethiopia - Tibebe, Dessie; Lemma, Dereje; Teshome, Gizachew (International Journal of Chemistry and Materials Research, 2019)
The purpose of this study was to determine the concentration of heavy metals in Lake Hayq water and fish muscles samples during dry and wet seasons. Samples of fish organs and water were collected from four sampling sites of Lake Hayq. An optimal procedure required 8 mL of (69%) HNO3 and 6 mL of (30%) H2O2 to mineralize powdered samples in open refluxed digestion vessels: 0.5 g of the fish body for 2:30 hrs at temperature of 130oc.Concentrations of six metals (Pb, Ni, Zn, Cd, Cu and Cr) in water and their accumulation in the edible tissue of Nile Tilapia were determined by FAAS. The results revealed that the average heavy metal concentrations in water samples were; Pb (0.006), Ni (0.018), Zn (0.083), Cd (0.004), Cu (0.1) and Cr (0.003) mg/L in the lake. The average concentration of heavy metals in fish samples were; Pb (2.02), Ni (2.29), Zn (55.52), Cd (1.57), Cu (11.18) and Cr (0.745) mg/Kg. Among the detected metals, zinc (Zn) showed a maximum accumulation in the edible muscle of Nile Tilapia fish from Lake Hayq. The concentrations of the metals (Pb, Zn, Cd, and Cu) were below the recommended limit by WHO, USEPA and FAO. For fish the highest accumulations of nickel (Ni) and chromium (Cr) concentration were observed above the recommended limit by FAO/ WHO. Application of the statistical t-test on heavy metal analysis has shown that there was no significant difference between fish as well as water samples of the lake for all sites.